Non-linear regulation of cardiac autonomic modulation in obese youths: Interpolation of ultra-short time series - Garner, David M.; Vanderlei, Franciele M. [UNESP]; Valenti, Vitor E. [UNESP]; Vanderlei, Luiz Carlos M. [UNESP] (Cambridge University Press (CUP), 2019)
Background: In this study, we applied ultra-short time series of interbeat intervals (RR-intervals) to evaluate heart rate variability through default chaotic global techniques with the purpose of discriminating obese youths from non-obese youth patients.Method: Chaotic global analysis of the RR-intervals from the electrocardiogram and pre-processing adjustments was undertaken. The effect of cubic spline interpolations was assessed, while the spectral parameters remained fixed. Exactly, 125 RR-intervals of data were recorded.Results: CFP1, CFP3, and CFP6 were the only significant combinations of chaotic globals when the standard conditions were enforced and at the level p<0.01 (or <1%). These significances were acheived via Kruskal-Wallis and Cohen's ds effects sizes tests of significance after Anderson-Darling and Lilliefors statistical tests indicated non-normal distributions in the majority of cases. Adjustments of the cubic spline interpolation from 1 to 13 Hz were revealed to be inconsequential when measured by Kruskal-Wallis and Cohen's ds, regarding the outcome between the two datasets.Conclusion: Chaotic global analysis was offered as a robust technique to distinguish autonomic dysfunction in obese youths. It can discriminate the two different groups using ultra-short data lengths, and no cubic spline interpolations need be applied.
Keywords: chaotic globals; cubic spline interpolation; Obese youths; ultra-short time series